Preclinical stiff heart is a marker of cardiovascular morbimortality in apparently healthy population - Fauvel, Charles; Bubenheim, Michael; Raitière, Olivier; Vallet, Charlotte; Belkacem, Nassima Si; Bauer, Fabrice (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: The prognostic significance of impaired left ventricular (LV) relaxation and increased LV stiffness as precursor of heart failure with preserved ejection fraction and death is still largely unknown in apparently healthy subjects. Methods: We constituted a cohort of 353 patients with normal ejection fraction (>45%) and no significant heart disease, based on a total of 3,575 consecutive left-sided heart catheterizations performed. We measured peak negative first derivative of LV pressure (-dP/dt) and operating chamber stiffness (Κ) using a validated equation. Patients were categorized as having: 1) normal diastolic function, 2) isolated relaxation abnormalities (-dP/dt > 1860mm Hg/sec and K <0.025mm Hg/ml), or 3) predominant stiff heart (K ≥0.025mm Hg/ml). Results: During a follow-up of at least 5 years, the incidence of the primary composite endpoint (death, major arterial event, heart failure, and arrhythmia) was 23.2% (82 patients). Compared to isolated relaxation abnormalities, predominant stiff heart showed stronger prognostic significance for all events (p=0.002), namely heart failure (HR, 2.9; p=0.0499), cardiac death (HR, 5.8; p=0.03), and heart failure and cardiac death combined (HR, 3.7; p=0.003). Conclusion: In this apparently healthy population referred to our center for cardiac catheterization, the prevalence of diastolic dysfunction was very high. Moreover, predominant stiff heart was a better predictor of cardiovascular outcomes than isolated relaxation abnormalities.